Fra biologidiskurs til miljødiskurs? – Pressedekningen av minoriteter i norske aviser fra 1902–2010 - Malene Paulsen Lie; Toril Aalberg (Norsk Medietidsskrift, 2014)
Abstract Has coverage of minorities in the Norwegian press moved from a static biology discourse rooted in racial thinking to a more dynamic discourse based on environmental and cultural factors? Based on a quantitative and qualitative content analysis of newspaper articles from the period 1902–2010, we show that press coverage early in the period frequently refers to biological aspects of minorities, while environmental and cultural factors increase in the later period. References to minorities culture in the final period, however, are among the most static, while early reference to skin complexion, etc., is less static than pure race-based thinking would suggest.